Pengaruh Disposisi Matematis terhadap Kemampuan Pemecahan Masalah dengan Pembelajaran Berbantuan Video - Ratna Natalia Mendrofa; Hasratuddin Hasratuddin; Bornok Sinaga (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study aims to describe the influence of mathematical disposition on problem-solving ability through video-assisted learning in seventh-grade mathematics at a junior high school in Gunungsitoli City. The research employed a quasi-experimental design, with class VII-A as the experimental group (n = 32) receiving video-assisted instruction and class VII-B as the control group (n = 32) using conventional methods. Data were collected through problem-solving ability tests and mathematical disposition questionnaires, administered as pre-tests and post-tests. Analysis was conducted using t-tests and linear regression analysis. Results showed a significant improvement in problem-solving ability in the experimental class compared to the control class, with gain scores of 0.50 and 0.25 respectively. For problem-solving ability, the experimental class improved from a pre-test average of 67.34 to a post-test average of 83.78, while the control class improved from a pre-test average of 66.22 to a post-test average of 73.84. The mathematical disposition analysis yielded scores of 79.31 for the experimental class and 72.06 for the control class. Findings indicate that students who participated in video-assisted learning demonstrated significant improvement in problem-solving ability compared to the control group. Furthermore, students' mathematical disposition positively correlated with this improvement. This suggests that the video-assisted learning approach has potential in facilitating the development of mathematical problem-solving skills, while acknowledging the role of mathematical disposition in the learning process.